OWN RESEARCH SOURCE OF METHODS OF TEACHING LITERATURE AND THE SOCIAL SIGNIFICANCE OF THIS SOURCE (Academicia Globe: Inderscience Research, 2024)
In this article, the methodology of teaching literature is an important element of the educational process, the importance of literary education, a unique research source that includes innovative approaches to teaching literary works, the influence of a literary text on cultural and social processes, literary educational methods covering the main aspects of analysis, including genre classification, methodological features, and cultural contexts of literary works are described.